Social identity switching: An investigation of non‐demographic identities with computational‐linguistic and self‐report measures. - Zinn, Anna Kristina; Lavric, Aureliu; Naserianhanzaei, Elahe; Koschate, Miriam (British Journal of Social Psychology, 2025)
Understanding potential costs of social identity switching contributes to our knowledge of how people manage their various group memberships in a fast‐paced and interconnected world. Recent research demonstrates that people can switch between demographic social identities seamlessly. The current studies advance this research by (1) moving beyond demographic identities to identities that are not perceptually distinguishable, (2) developing a new identity switching paradigm based on an implicit computational linguistic style measure of salience and (3) including self‐report measures of salience, task difficulty and performance. In two within‐subjects studies (N = 211; N = 220), a short writing task was used to prompt a switch from participants' parent identity to their feminist identity or a repetition of the feminist identity. Findings from the implicit measure revealed no identity activation 'cost' in the switch relative to the repeat condition, consistent with previous findings for demographic identities. In contrast, we found evidence for lower self‐reported salience of the feminist identity in the switch compared to the repeat condition. Furthermore, Study 2 found little difference in self‐rated performance or task difficulty between conditions, indicating that switching identities does not affect self‐rated performance. The results illustrate a new paradigm for investigating social identity switching.